2017
DOI: 10.5530/ijopp.10.2.25
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anti-tubercular Drugs and Impact of Glycemic Status in Patients with Tuberculosis and Concomitant Diabetic- Tuberculosis Patients

Abstract: India is a key nation which is endemic and epidemic to tuberculosis and diabetes. An association between diabetes and TB is biological plausible, where diabetes impairs the immune system and making it harder for the body to fight against infection. Methodology: Patients on DOTS therapy in continuation phase of anti-TB therapy, Patients with TB and Diabetes and Patients with TB alone were included in the study. Blood samples were collected and Fasting Blood Glucose (FBG), Post Prandial Glucose (PPG) and Glycate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…The antituberculous treatment effectiveness was considerably lower in the diabetic group, through a higher mortality rate compared with non-diabetic patients. The obtained results were similar to other studies, that identified a high rate of death and treatment failure [6,7,[11][12][13][14][15][16][17]23,24]. All patients with DM received an individualized treatment, but in every fourth the glycemic control was not achieved.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The antituberculous treatment effectiveness was considerably lower in the diabetic group, through a higher mortality rate compared with non-diabetic patients. The obtained results were similar to other studies, that identified a high rate of death and treatment failure [6,7,[11][12][13][14][15][16][17]23,24]. All patients with DM received an individualized treatment, but in every fourth the glycemic control was not achieved.…”
Section: Discussionsupporting
confidence: 88%
“…Our research established that TB was diagnosed more often in patients with complications, in which the FVPG exceeded the normal limit. In the literature many studies established that patients with uncontrolled blood glucose level have high risk for occurrence of TB [11][12][13][14][15]23,25]. Although men are significantly more at a risk for contracting and dying from TB than women, our research established a similar distribution of the diabetic patients in groups according to the sex.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations